Dilema Kehendak Hidup: Menggali Pemikian Scopenhauer tentang Penderitaan dan Euthanasia - Jebar, Sirilus; Darmingtri, Yonas; Melo, Paulus; Satyawardhana, Fransiskus Antonius Dimas (Universitas Negeri Yogyakarta, 2024)
This article focuses on analyzing euthanasia cases through the perspective of Arthur Schopenhauer, related to his concept of the will to live. Schopenhauer argues that, in order to fulfill the will to live, humans cannot avoid suffering. This research aims to analyze the relevance of Schopenhauer's views to the phenomenon of euthanasia, a controversial practice aimed at ending the suffering of terminally ill people. The research method involves a philosophical analysis of Schopenhauer's works as well as a study of various ethical, legal, and moral arguments related to euthanasia. The author also uses a literature study method in the form of a literature review of books, journals, and other sources that support this article. The analysis of euthanasia cases is also carried out based on various existing sources and phenomena that are often discussed on social media and become public conversations. This article presents a novelty by looking at euthanasia cases from Schopenhauer's informative perspective, which can be an enlightenment for those who have erroneous views on this issue. The main findings of this study suggest that Schopenhauer's pessimistic view of life, which sees suffering as an inevitable aspect of human existence, provides an in-depth understanding of the suffering that can trigger consideration of euthanasia.Keywords: Arthur Schopenhauer, euthanasia case, will to live, human consciousness